Study of sociodemographic profile and pattern of gynaecological malignancies in a tertiary care center - Chaudhary, Sushila; Singhal, Savita Rani; ., Latika; Gupta, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gynaecological malignancies are second most common cancer of females after cancer breast. Carcinoma cervix is the commonest gynaecological malignancy in developing countries while in developed countries, ovarian cancer is the commonest gynaecological malignancy. Appropriate screening and timely diagnosis can save many lives. The objective of this study was to study socio-demographic profile of patients presenting with gynaecological malignancy. And to study presenting symptoms and pattern of gynaecological malignancies in them Methods: It was a retrospective record based study from December 2011 to December 2015. Various parameters from Case records of patients with gynaecological malignancies who visited outpatient department of unit IV were retrieved and analysis done. Results: In our study, most of the patients (30.52%) belonged to age group of 51-60 years, were multiparous (94.21%), Illiterate (67.3%) and belonged to rural background (65.28%). Most of the patients of cancer cervix had their presenting complaint as post-menopausal bleeding (48.38%), followed by excessive white discharge (33.87%). Majority of patients (65.26%) had cancer cervix, were in FIGO stage II .Commonest histopathological type was squamous cell carcinoma. Conclusions: Most common gynaecological malignancy in India is carcinoma cervix. Proper screening and timely diagnosis can save many lives.